2004
DOI: 10.1051/0004-6361:20034511
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of the two large flares from SGR1900+14 with theBeppoSAXGamma-Ray Burst Monitor

Abstract: Abstract. We report on spectral and temporal results of the 40-700 keV observations, obtained with the Gamma-Ray Burst Monitor (GRBM) on board BeppoSAX, of the two large flares from the Soft Gamma-ray Repeater SGR 1900+14 occurred on August 27, 1998 and April 18, 2001. From their intensity, fluence and duration, the first one was classified as "giant" and the second as "intermediate".The spectral results have been obtained with an improved response function of the GRBM. We find that the two events have similar… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2004
2004
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 59 publications
1
28
0
Order By: Relevance
“…The strongest of these "intermediate" flares was observed on April 18, 2001 from SGR 1900+14 [108,74]. It lasted about 40 s and showed pulsations at the NS rotation period, as in the tails of giant flares, but it lacked an initial spike.…”
Section: Bursts and Flaresmentioning
confidence: 99%
“…The strongest of these "intermediate" flares was observed on April 18, 2001 from SGR 1900+14 [108,74]. It lasted about 40 s and showed pulsations at the NS rotation period, as in the tails of giant flares, but it lacked an initial spike.…”
Section: Bursts and Flaresmentioning
confidence: 99%
“…Integrating over the entire flare assuming isotropic emission, at least 10 44 erg were released in hard X-rays above 15 keV (Mazets et al 1999). SGR 1900+14 also emitted another less intense flare on 18 April 2001 (Feroci et al 2003;Guidorzi et al 2004), which based on its energetics was classified as an "intermediate" flare.…”
Section: Sgr 1900+14mentioning
confidence: 99%
“…The luminosity of this giant burst was estimated to be greater than 10 44 ergs s À1 . Another very bright flare from SGR 1900+ 14 was observed on 2001 April 18 (Guidorzi et al 2004); it was shorter and less intense than that of 1998, but it too showed periodicity. Given that both its duration of $40 s and its peak luminosity of $10 42 ergs s À1 fell in between the common recurrent bursts and the giant flare, this burst was classified as an intermediate flare.…”
Section: Introductionmentioning
confidence: 96%